Using Blockchain for Managing Zakat Distribution: A Juristic Anlytical Study - Tarkhani Ayoob Ibrahim Ahmed; Mohamad Sabri B Zakaria (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
This research study will endeavour, in principle, to make a significant contribution to the field of zakat management. It basically aims at suggesting a unique approach that would be practical and effective in managing the zakat sector through blockchain technology. The paper additionally deals with several current challenges encountered in the adopted approaches of managing zakat in Muslim societies; including, inter alia, inefficiency, lack of transparency in terms of fund collection, managing and distribution. In the meantime, it is hoped that blockchain technology would be adoptable effectively to address such relevant problems in a transparent and immutable manner in effect. This article will basically adopt the qualitative and data collection method. Main data will be collected through articles and dissertations because related data mainly exists in the articles and thesis rather than books. This study assumes certain fiqhi (Islamic jurisprudence) issues of using blockchain for managing zakat distribution such as establishing full-possession or tamlīk (Ownership), transporting zakat funds, and transferring zakat funds directly without ruler or government interference. The findings of this paper indicate that providing a novel method, which would contribute to reducing routine procedures and playing an effective role to put an end to the administrative and financial inefficiencies that have paralysed zakat institutions. The main significant aspect of this research will be establishing an active Technological Department for the purpose of serving charitable projects and reconstructing the trust between groups managing zakat and donors